(untitled) (Swiss Medical Weekly, 2021)
Osteoarthritis of the trapeziometarcarpal joint, also called rhizarthrosis, is a common finding in the second half of life. It has a higher prevalence in females and is of growing importance in ageing societies. A variety of conservative and surgical treatment options are known, including conservative treatment up to joint replacement. Without treatment, rhizarthrosis can lead to disabling pain and loss of hand function. The goal of this overview of treatment options is to present a stepwise approach that can be initiated by any physician. Treatment of trapeziometacarpal osteoarthritis should be started early with conservative measures such as splinting and physical therapy, which can be supplemented by oral and topical analgesics and local infiltrations subsequently. If all of these interventions do not provide sufficient relief, referral to a hand surgeon should be considered. Surgical strategies vary from arthroscopic debridement over trapeziectomy, with or without tendon interposition and ligament reconstruction, to interposition implants and total joint replacements. The planned intervention should be based on clinical and subjective functional limitations and associated degenerative changes, as well as the patient’s expectations and needs. The goal of this paper is to develop a treatment algorithm, leading to higher levels of patient functionality and satisfaction. Below we discuss the current literature and point out key treatment options used in our department.